PENGEMBANGAN SISTEM MEMBACA AL-QUR’AN DENGAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Herman, Suherman; Samsuni, Sunny; Fathurohman, Fathurohman (ILKOM Jurnal Ilmiah, 2019)
Al-Qur'an is the Holy Book which is the main and first source in Islamic teachings. It is important for us as Muslims to learn about how to read the Qur'an properly. This research  uses two method approach namely Multimedia System Development method and learning method used is to use Tartil method. By using this two-method approach it is hoped that it will be more interesting for students to read and be able to accelerate how to read the Qur'an properly. The results of this research are in the form of an android-based application that can help to learn and read the Al-Qur’an properly. This application is tested using the Black Box method that shows all functions are running properly 100% according to what is expected.. The results show 85% progressed after using the application and only 15% did not progress.